A Comparative Study of Postnatal Care Practices among Mothers in Rural and Urban Communities of Kano State, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Postnatal care remains the most neglected component of maternal and child health. It is determined by postnatal practices, which may be beneficial, innocuous or harmful as prevalent in low and middle income countries including Nigeria.Aim:To compare postnatal care practices among mothers in urban and rural communities.Settings and Design:A comparative cross-sectional design was used to assess postnatal care practices among 130 mothers each in urban and rural communities of Kano using multistage systematic sampling.Materials and Methods:Data were collected from mothers who delivered a live baby within the preceding year using an interviewer administered semi-structured questionnaire.Statistical analysis used:Data collected was analysed using the SPSS Statistics for Windows, Version 21.0.Results:Findings show poor postnatal care practices like delay in initiation of breastfeeding (77.2% and 88.4%, respectively), poor cord care (97.6% and 100%, respectively) and ingestion of potash gruel (35.4% and 65.9%, respectively) were abundant. Postnatal care practice was significantly associated with respondents' education and husband's education in the urban area (and age of respondents in the rural community (P < 0.05). Marital setting was the only predictor of postnatal practice (odds ratio = 0.25, 95% confidence interval [0.09–0.69]), where mothers in a monogamous setting had a 75% likelihood of good practice as compared to their polygamous counterparts.Conclusion:The preponderance of bad postnatal practices found among mothers in both urban and rural settings indicates the level of danger that mothers and their newborns are exposed to in the studied communities.